Análisis financiero de la compañía de taxis Calumatax S.A. del cantón Caluma Provincia de Bolívar, de los periodos 2019 – 2020 - Bonilla Naranjo, Victoria Stefany (2021)
The Company de Taxis CALUMATAX SA is an institution that provides taxi services to Calumeña citizens for around twenty-three years, resides between Humberto del Pozo and Vinicio Noboa streets of the Caluma canton belonging to the Province of Bolívar, said organization has evolved In the economic, administrative, financial and especially labor fields, however, the economic and accounting effects derived from the health emergency that occurred during fiscal years 2019 and 2020 constitute the central reason for this research work. The execution of the development is conformed by the recognition of the general aspects of the institution, the problems together with the bibliographic citations that support the theories and conceptualizations related to the subject of study and that are presented as causes of the financial evaluation carried out, in addition to the use of analysis tools and financial ratios that made it possible to measure the accounting and financial variations resulting from the mathematical calculation between the figures of the financial statements corresponding to fiscal years 2019 and 2020. The methodology used is exploratory, the financial examination is carried out through horizontal analysis, in addition to the financial ratios of both liquidity and profitability, the research work is part of the research sub-line of the accounting and auditing career corresponding to the financial, tax and social commitment management. It should be noted that the interpretation of the results derived from the financial analysis constitutes the most relevant synthesis for the corporate governance of the company because it allows the maximization of the value of the organization, since the shareholders expect that the value of their company will increase depending on of the time either with respect to the assets, income or the patrimonial group.